Development of a Care Model for High-Risk Pregnant Women in the Digital Transformation Era - ส่งเสริมพงษ์ สรภัญ; รอดโพธิ์ทอง จิดาภา; พิริยะอุดมพร ปยารี (Journal of Health Science of Thailand, 2023)
The objectives of this study were to develop and evaluate the effectiveness of a care model for high-risk pregnant women in the age of digital transformation. It was designed as a research and development study involving high-risk pregnant women attending antenatal services at Pakkred Hospital, Nonthaburi Province, from August to November 2022. The research was conducted in two distinct phases: the phase 1 was on model development which included assessing the current scenario and observing the environment dedicated to high-risk pregnancy care. Comprehensive interviews were conducted by a multi-disciplinary team with the high-risk pregnant women. The Standford d.school’s design thinking process was applied in the process. A hospital committee was formed to develop the model through facilitated group discussions aiming at refining the model prior to its actual implementation. The phase 2 was on the evaluation of the model efficacy in which we assessed the knowledge of high-risk pregnant women participating in the project, specifically their understanding and practices before and after utilizing the model; and recorded all complications that arose during their participation. In adddition, we evaluated their satisfaction levels post-usage. The tools implemented in this research include a record form on highrisk pregnancy knowledge and practice evaluation to prevent complications during pregnancy. Data were analyzed by using descriptive statistics and paired samples t-test. It was found that post-adoption of the model, the high-risk pregnant women showed significantly improved knowledge scores. Their self-care practices for preventing complications during pregnancy were significantly enhanced compared to the pre-model implementation phase (p<0.001). The participating high-risk pregnant women demonstrated a high level of satisfaction.